2004
DOI: 10.2175/106143004x151554
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Community‐Level Physiological Profiles of Domestic Wastewater Following Treatment by Small Constructed Subsurface Flow Wetlands

Abstract: Seasonal treatment performance of small-surface flow wetlands was evaluated during their second operational year and compared with community-level physiological profiles (CLPP) of the heterotrophic bacterial community obtained from sole-carbon source utilization patterns in BIOLOG GN (Haywood, California) microplates. The CLPP patterns varied significantly by season, indicating reduced functional diversity in the heterotrophic community during warmer months of active plant growth (April through October). Princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Recently, Ros et al (2008) have found a very low diversity within the Biolog plates. Nevertheless, the communitylevel physiological profile (CLPP) technique has been widely used in part because it is simple using an automated measuring apparatus, and the CLPP procedure measures the community structure of the bacteria that are able to grow in the culture conditions of the Ecoplate (Buyer et al, 2002;Garland et al, 1997) and has been shown in some cases to be as sensitive as or more sensitive than measuring microbial biomass and respiration (Johnson et al, 1998), it, therefore, has been used to detect heterotrophic microbial communities among and within wastewater-treatment systems (Collins et al, 2004;Hadwin et al, 2006;Hench et al, 2004;Nurk et al, 2005;Osem et al, 2007;Victorio et al, 1996;Weber et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ros et al (2008) have found a very low diversity within the Biolog plates. Nevertheless, the communitylevel physiological profile (CLPP) technique has been widely used in part because it is simple using an automated measuring apparatus, and the CLPP procedure measures the community structure of the bacteria that are able to grow in the culture conditions of the Ecoplate (Buyer et al, 2002;Garland et al, 1997) and has been shown in some cases to be as sensitive as or more sensitive than measuring microbial biomass and respiration (Johnson et al, 1998), it, therefore, has been used to detect heterotrophic microbial communities among and within wastewater-treatment systems (Collins et al, 2004;Hadwin et al, 2006;Hench et al, 2004;Nurk et al, 2005;Osem et al, 2007;Victorio et al, 1996;Weber et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…That being said, there are relatively few microbial community function methodologies available for TWs. Hench et al [28] first used community level physiological profiling, borrowing from soil scientists and the development of micro-titre plates for soil bacteria differentiation [29,30]. It was, however, not until recently (for example see Button et al [19]) that the carbon sources on the plate were truly considered as measures for organic degradation and used in data interpretation and TW optimization recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…For each basin, the top 5 cm of five sediment samples taken in June 2014 were pooled together to get a representative sample per basin and stored at 4°C until further processing the next day. Sediment samples were diluted with sterilized demi water to obtain a dilution of 1:7, shaken by hand for a minute to detach bacteria from sediment particles and centrifuged at 1000 g for 15 min, after which the supernatant was diluted with sterilized demi water to a final dilution of 1:87 (adapted from Hench et al 2004). BIOLOG plate wells were inoculated with 150 μl bacterial suspension and incubated in the dark at 15°C to simulate natural conditions.…”
Section: Decomposer Communitymentioning
confidence: 99%